An estimation of the health and climatic impacts of household biomass consumption across Nigeria in 2018 - Jessica Slater; Eve Palmer; Maria Yetano-Roche; Ewah Eleri; Christopher S Malley (Environmental Research: Health)
In 2021, Nigeria became the first country in the world to state, quantitatively, how implementing their nationally determined contribution (NDC) to mitigate climate change could improve health. Nigeria’s NDC stated that an estimated 30 000 premature deaths could be avoided annually by 2030 due to reduction in household air pollution caused by burning wood and charcoal for cooking. As Nigeria moves to implement its climate change commitments, there are two key questions that this paper aims to address. Firstly, across Nigeria, where are the greatest health burdens from household air pollution that could be targeted to achieve these health benefits, and secondly, to what extent does wood fuel consumption drive greenhouse gas emissions from the forestry and land use (FOLU) sector? To explore these questions this paper utilizes available statistical data on households primary cooking fuel choice at the state level in Nigeria to estimate the health impact from household air pollution due to households cooking using wood and charcoal. It also provides an estimate of the total wood fuel demand in the country and from this provides an estimate of the carbon dioxide emissions from the FOLU sector associated with these households’ biomass use. In 2018, it was estimated that of the almost 116 thousand premature deaths attributable to household air pollution in 23% occurred in 3 states in Northern Nigeria. The biomass consumption for household energy consumption across Nigeria was estimated to contribute 78% of the 151 million tonnes of carbon dioxide emissions estimated within this analysis to be due to the FOLU sector in Nigeria. Hence action targeted at transitioning households to modern cooking fuels and technologies can have a large impact on achieving the dual climate and health goals Nigeria has set itself within its climate change commitment.